Traditional Institutions as Instrument for Rural Development in Ilorin Emirate of Kwara State, Nigeria - Mohammed, Idris Danjuma; Towoju, Adedoyin John; Jamiu, Mubarak Sulaiman (NIU Journal of Humanities, 2023)
The study examined the roles of the traditional institutions in the community development with reference to llorin Emirate in Kwara State as well as bringing the effects and impacts of traditional institutions on rural and socio-economic development to the people of Ilorin Emirate because the role of Traditional Institutions in community development ranged from providing good leadership as Custodian and repository of the community, to mobilize physical, human and financial resources for the local development at large. This paper is situated within the qualitative method of social research. The paper, which is theoretical in nature basically extract its arguments from secondary sources of data including journals and other related policies, textbooks and publications. To improve on the reliability and validity of the paper, multiple secondary sources were used to harmonize the risk of error. The paper concludes that, traditional rulers play a very significant role of informally managing conflict and peace-making meetings when matters get out of hand, they also serve as advisory role to the local council. On the basis of these findings, it was recommended among others that traditional rulers should be adequately empowered financially, socially and materially; as this would go a long way to influence their effectiveness in grass root mobilization for rural development. Keywords: Ilorin Emirate, Traditional institutions, Rural Development